Respuesta :
3(x + 1) = −2(x − 1) + 6
3x + 3 = -2x + 2 + 6
5x = 5
x = 1
answer
x = 1
3x + 3 = -2x + 2 + 6
5x = 5
x = 1
answer
x = 1
To solve for x, you would need to distribute, and then simplify. So we have the equation 3(x+1) = -2(x-1) + 6.
Step 1: Use the distributive property. Multiply the outside number to both terms inside the parenthesis to get 3x + 3 = -2x + 2 + 6.
Step 2: Simplify and combine like terms. 3x + 3 = -2x + 8.
Step 3: Now you can use the addition property of equality, and add 2x to both sides, (to cancel the x variable on the right) so you get 5x + 3 = 8.
Step 4: Use the subtraction property of equality and subtract 3 from both sides to get 5x = 5.
Step 5. Finally, use the division property of equality and divide both sides by 5 to get x = 1.
Hope this helps! Let me know if you don't understand something or need more help! :D
PS: You can also check your answer. As per my answer, x is equal to 1. Plug that into both sides. You can distribute again and get 3 + 3 = -2 + 2 + 6. This is a true statement as 6 is equal to 6. That is how you check your answer.
Step 1: Use the distributive property. Multiply the outside number to both terms inside the parenthesis to get 3x + 3 = -2x + 2 + 6.
Step 2: Simplify and combine like terms. 3x + 3 = -2x + 8.
Step 3: Now you can use the addition property of equality, and add 2x to both sides, (to cancel the x variable on the right) so you get 5x + 3 = 8.
Step 4: Use the subtraction property of equality and subtract 3 from both sides to get 5x = 5.
Step 5. Finally, use the division property of equality and divide both sides by 5 to get x = 1.
Hope this helps! Let me know if you don't understand something or need more help! :D
PS: You can also check your answer. As per my answer, x is equal to 1. Plug that into both sides. You can distribute again and get 3 + 3 = -2 + 2 + 6. This is a true statement as 6 is equal to 6. That is how you check your answer.